COMPARING THE CLINICAL OUTCOMES OF LUMBAR TRANSFORAMINAL VS INTERLAMINAR EPIDURAL STEROID INJECTIONS IN A REGISTRY COHORT - YOUNIS, W; AZIZ, L; DAR, SR; CHAUDHARY, WA; BAKAR, A; NAEEM, B (Biological and Clinical Sciences Research Journal, 2024)
Epidural steroid injections are a safe and effective treatment for acute low back pain associated with radicular pain. Objective: The main objective of the study is to find the clinical outcomes of lumbar transforaminal vs interlaminar epidural steroid injections in a registry cohort. Methods: This prospective cohort study was carried out at Ghurki Trust Teaching Hospital, Lahore, over one year, from June 2023 to June 2024. A total of 185 patients were included in the study. Patients aged >18 years and presented with symptoms of lumbar radiculopathy due to lumbar disc herniation, spinal stenosis, or degenerative disc disease were included in the study. Results: The mean age of the TFESI group was 45.6 ± 10.3 years, while the ILESI group had a mean age of 46.2 ± 9.8 years (p = 0.67). The gender distribution was also comparable, with 55 males and 37 females in the TFESI group, and 58 males and 35 females in the ILESI group (p = 0.78). Baseline pain intensity (VAS score) and disability (ODI score) were similar between the two groups, with no significant differences in VAS (7.6 ± 1.1 vs. 7.5 ± 1.2, p = 0.58) or ODI (52.4 ± 10.2 vs. 51.9 ± 9.9, p = 0.71). In the TFESI group, 52.2% of patients had lumbar disc herniation, compared to 49.5% in the ILESI group (p = 0.69). Lumbar spinal stenosis was diagnosed in 32.6% of patients in the TFESI group and 34.4% in the ILESI group (p = 0.81). Conclusion: It is concluded that both lumbar transforaminal epidural steroid injections (TFESI) and interlaminar epidural steroid injections (ILESI) are effective in the management of lumbar radiculopathy, leading to significant reductions in pain and improvements in functional outcomes.